Political economy, nationalistic populism, and immigration in today's world - Brux, Jacqueline Murray, author. Link
1 online resource
Keywords: Political Economy, Nationalistic Populism, and Immigration in Today's World: A Primer for the Social Sciences is a core text for a multidisciplinary range of courses in economics, political science, sociology, international studies, public policy, and the social sciences.The text weaves together an understanding of the interconnected topics of global nationalistic populism, authoritarianism, immigration, conditions in developing countries, social systems and safety nets, diversity, and ultimately, happiness as measured by global happiness surveys.The text is designed for a global audience through the use of examples and case studies in a manner that is clear to students and provides all prerequisite knowledge for undergraduates. It includes content on countries across the developing world, Europe, Canada, and the United States. There is considerable emphasis on the politics and ideologies of Europe and the United States and how these relate to immigration and impact each other.